The Fungimetarhizium Anisopliae as a Biocontrol for Ectoparasite Mites and Ticks in Livestock - Riza Zainuddin Ahmad (Indonesian Center for Animal Research and Development, 2004)
Metarhizium anisopliae has been known as a biological agent that can kill and control pests especially arthropods. Recently the efforts on controlling arachnid: mites and scabies known as ectoparasites for ruminants have been done by using this fungus. This fungus can be used as a biological control on ectoparasite since it is not harmful for human and animal health. At the same time the availability of microbes as the Indonesian germ plasm especially fungi is sufficient to support the development ofM. anisopliae as a biological control agent, and eventually its development prospect as a controlling for ticks and mites in the future is promising. Key words: Metarhizium anisopliae, control biology, ectoparasite